A Conceptual Framework for e-Commerce Personalization in Small Medium Enterprise’s - Johan Reimon Batmetan; Trudi Komansilan; Sondy C Kumajas (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Information overload on e-commerce sites or applications makes users spend more resources than they should. Buyers should be able to use it according to their own habits, needs, wants and beliefs. Personalization of e-commerce is a solution that can be used to overcome this problem. In this paper, the researcher creates a framework for personalizing e-commerce, especially for small and medium enterprises. This framework consists of the customer behavior assumption, technology requirement and business assumption. The customer behavior assumption contains an approach to the habits/nature of the buyers themselves. By understanding this, e-commerce can offer something suitable and different for each person. Meanwhile, with technology requirements, e-commerce is able to adapt to the development of content and scalability of e-commerce itself. To make users feel comfortable and willing to go back to shopping at the same e-commerce, the business assumption is another component in this framework. We conclude that the use of this personalization framework can have a major impact on increasing user retention in e-commerce.